Intelligent Tutoring Systems Authoring Tools For Nonprogrammer Authors: A Systematic Review - Nur Rokhman; Syeh Abidin Kobar (SISFORMA, 2022)
Many studies have been shown that Intelligent Tutoring Systems (ITSs) contribute to a remarkable improvement in the educational outcomes of students. Several authoring tools have been developed to contribute to making ITSs easier to build and widespread. However, there is still a lacks of current understanding in the ITSs community on how authoring tools could support nonprogrammer authors to build ITSs. This study uses a systematic literature review (SLR) method to identify primary empirical studies for nonprogrammers regarding the usage of ITSs authoring tools. The concern of this study is summarizing and analyzing the state of the art of the development of authoring tools. This study identifies the ITSs components and types that can be authored, the technologies used, and also search for proof of the advantages of ITSs authoring tools as well.